Percutaneous Drainage of Intraabdominal Abscesses. - Moncayo A., Fernando (Revista Universidad de Guayaquil, 2012)
We report the results and complications of percutaneous drainage of intraabdominal abscesses performed by surgeons at an Emergency Unit. A prospective protocol was designed for its application in all patients with suspected intraabdominal abscesses evaluated at the Emergency Unit of the Hospital Guayaquil “Abel Gilbert Pontón” and tú patients transferred fron other Units for evaluation. Between January 2009 and December 2010, 30 patients; our results show that percutaneous drainage of abdominal abscesses perfomed by sugeons is a safe and efficient method with a low index of complications and a succes rate of more than 93% either as the only treatment or associated to antibiotics. The resuld was curative in 70% of cases, paliative in 23% and fail in 7% . In many cases, it should be considered the treatment of choice, but there are certain circumstances that require specific approaches and methods. Typical abscesses within solid parenchymal organs or those in the peritoneal spaces can be reliably detected by imaging techniques and efficiently drained. Percutáneos drainge, has been established as a viable alternative to surgical intervention. This method can resolve the abscess or improve the patient clinical status to undergo elective surgery